2020
DOI: 10.1055/s-0040-1716669
|View full text |Cite
|
Sign up to set email alerts
|

Depression Is Not Independently Associated with a Clinically Worse Functional Improvement but Associated with a Lower Reported Satisfaction Rate after Total Knee Arthroplasty

Abstract: The aim of this study was to assess whether depression had a clinically significant influence on the functional improvement of total knee arthroplasty (TKA) according to the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score, and whether it influences patient satisfaction at 1 year. A retrospective cohort of 3,510 primary TKA was identified from an arthroplasty database. Patient demographics, comorbidities, WOMAC, and Short Form-12 (SF-12) scores were collected preoperatively and 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Several studies have shown that delaying hip and knee arthroplasty results in a worse preoperative functional score which is subsequently associated with a worse postoperative health state 17 and lower rate of patient satisfaction. 18 - 20 The effect of the COVID-19 pandemic on patient outcome will likely be difficult to quantify in the future, with patients living for longer with their disability and potentially having a worse outcome due to their delayed surgery. 17 , 21 This should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that delaying hip and knee arthroplasty results in a worse preoperative functional score which is subsequently associated with a worse postoperative health state 17 and lower rate of patient satisfaction. 18 - 20 The effect of the COVID-19 pandemic on patient outcome will likely be difficult to quantify in the future, with patients living for longer with their disability and potentially having a worse outcome due to their delayed surgery. 17 , 21 This should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that there are other ways to intervene, pre-and postoperatively, to improve satisfaction and outcome in TKA. Multiple preoperative factors have been associated with low postoperative satisfaction such as preoperative depression, preoperative opioid use, unrealistic preoperative expectations, and poor communication [1,[5][6][7]. Perhaps interventions on factors such as these can be more impactful on subjective TKA outcomes and less costly than introducing new technology.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%